2016
DOI: 10.18632/oncotarget.8626
|View full text |Cite
|
Sign up to set email alerts
|

The novel tankyrase inhibitor (AZ1366) enhances irinotecan activity in tumors that exhibit elevated tankyrase and irinotecan resistance

Abstract: BackgroundDysregulation of the canonical Wnt signaling pathway has been implicated in colorectal cancer (CRC) development as well as incipient stages of malignant transformation. In this study, we investigated the antitumor effects of AZ1366 (a novel tankyrase inhibitor) as a single agent and in combination with irinotecan in our patient derived CRC explant xenograft models.ResultsSix out of 18 CRC explants displayed a significant growth reduction to AZ1366. There was one CRC explant (CRC040) that reached the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…Although it seems that MK1775 monotherapy could achieve an anticancer effect in p53 mutant colonic cancer cells, the dosage for treatment is still a challenge, as the toxicity of agents targeting the cell cycle checkpoint is big problem. Combination with other chemotherapy drugs is a better choice as a first-line chemotherapy regime in metastatic colonic cancer (25), and a number of studies are seeking the proper strategy to increase the sensitivity of cancer cells to the cytotoxicity effect (26)(27)(28). In the present study MK1775 was demonstrated to increase the sensitivity of cells to the effect of irinotecan both in HT29 and SW480, and resulting in increased γ-H2AX and cleaved-caspase 3.…”
Section: Discussionmentioning
confidence: 52%
“…Although it seems that MK1775 monotherapy could achieve an anticancer effect in p53 mutant colonic cancer cells, the dosage for treatment is still a challenge, as the toxicity of agents targeting the cell cycle checkpoint is big problem. Combination with other chemotherapy drugs is a better choice as a first-line chemotherapy regime in metastatic colonic cancer (25), and a number of studies are seeking the proper strategy to increase the sensitivity of cancer cells to the cytotoxicity effect (26)(27)(28). In the present study MK1775 was demonstrated to increase the sensitivity of cells to the effect of irinotecan both in HT29 and SW480, and resulting in increased γ-H2AX and cleaved-caspase 3.…”
Section: Discussionmentioning
confidence: 52%
“…The TNKS1/2 enzymes regulate Axin2 degradation by PARylation, a mechanism which was elucidated in Huang et al (2009). Results from recently developed TNKS1/2 inhibitors have shown stabilization of Axin2 protein, decrease in Axin2 mRNA, and Wnt inhibitory activity, comparable to the observed effects of FH535 in OS (Bao et al, 2012; Quackenbush et al, 2016). Inhibitors of TNKS1/2 block Wnt signaling by reducing the PARylation of Axin2 by TNKS1/2.…”
Section: Resultsmentioning
confidence: 90%
“…Over the past decade, various tankyrase inhibitors have been developed, some of which have been adapted to in vivo administration in preclinical models . Among such inhibitors, G007‐LK is one of the most studied tankyrase inhibitors in vivo, although it has only been given i.p .…”
Section: Discussionmentioning
confidence: 99%
“…IWR‐1 is another tankyrase inhibitor, initially identified as an Axin stabilizer . Although XAV939 and IWR‐1 are not suitable for in vivo experiments owing to their pharmacokinetic problems, several tankyrase‐specific inhibitors for in vivo administration have been developed, including G007‐LK, NVP‐TNKS656, K‐756, AZ1366, G‐631 and JW55 . G007‐LK inhibits proliferation of the colorectal cancer cells COLO‐320DM and SW403, both harboring truncated APC mutations, but not HCT‐15 and DLD‐1 cells, which also have truncated APC mutants .…”
Section: Introductionmentioning
confidence: 99%